The MTA1 subunit of the nucleosome remodeling and deacetylase complex can recruit two copies of RBBP4/7. (18th May 2016) - Schmidberger, Jason W.; Sharifi Tabar, Mehdi; Torrado, Mario; Silva, Ana P. G.; Landsberg, Michael J.; Brillault, Lou; AlQarni, Saad; Zeng, Yi Cheng; Parker, Benjamin L.; Low, Jason K. K.; Mackay, Joel P.
Abstract: The nucleosome remodeling and deacetylase (NuRD) complex remodels the genome in the context of both gene transcription and DNA damage repair. It is essential for normal development and is distributed across multiple tissues in organisms ranging from mammals to nematode worms. In common with other chromatin‐remodeling complexes, however, its molecular mechanism of action is not well understood and only limited structural information is available to show how the complex is assembled. As a step towards understanding the structure of the NuRD complex, we have characterized the interaction between two subunits: the metastasis associated protein MTA1 and the histone‐binding protein RBBP4. We show that MTA1 can bind to two molecules of RBBP4 and present negative stain electron microscopy and chemical crosslinking data that allow us to build a low‐resolution model of an MTA1‐(RBBP4)2 subcomplex. These data build on our understanding of NuRD complex structure and move us closer towards an understanding of the biochemical basis for the activity of this complex.